The Influence Of Brand Image, Brand Awareness, and Brand Loyalty On Purchasing Decisions With Purchase Intention As A VariableIntervening (Case Study On MotorHonda Brand In Wonosobo) - Ida Bagus Nyoman Udayana; Hutami, Lusia Tria Hatmanti Hutami; Nurseto, Bangkit Adhe Nurseto (Economos : Jurnal Ekonomi dan Bisnis, 2024)
The purpose of this study was to find out how brand image, brand awareness, and brand loyalty influence purchasing decisions with purchase intent acting as an intermediary variable (Case study on Honda motorcycles in Wonosobo). Questionnaire samples from 100 participants were distributed during the study process in Wonosobo. SPSS 26 is used to analyze data. The results of this study show that Brand Image has an influence on Purchase Intent with a significance value of 0.001. Brand Awareness has an influence on Purchase Intent with a significance value of 0.006. Brand Loyalty has an influence on Purchase Intent with a significance value of 0.000. Brand Image has no influence on the Purchase Decision with a significance value of 0.669. Brand Awareness has no influence on Purchase Decisions with a significance value of 0.071. Brand Loyalty has no influence on Purchase Decisions with a significance value of 0.084. Purchase Intent influences Purchase Decision with a significance value of 0.000.